TRANSLATING DIALECTS AND SOCIOLECTS: STRATEGIES FOR PRESERVING SOCIAL IDENTITY IN LITERARY TRANSLATION (Web of Teachers: Inderscience Research, 2026)
The act of translating dialects and sociolects in literary texts stands as one of the most challenging yet essential aspects of literary translation studies. Literary works are, by their very nature, more than simple narrative structures; they are echoes of diverse societies, cultures, and historical realities. Deep within the fabric of literature, the nuanced tapestry of dialects and sociolects breathes life into characters, settings, and the broader social context in which a narrative unfolds. To ignore these linguistic markers during translation is to lose a crucial dimension of the text’s meaning, intent, and social identity.